Alternative Forms of Mineral Taxation, Market Failure and the Environment - Muzondo, Timothy (IMF Working Papers; Working Paper, 1992)
This paper examines the environmental effects of mineral taxes in a framework that recognizes the importance of rates and cumulative externalities and proposes an appropriate corrective tax. It concludes that mineral resources taxation should combine neutral taxes with a dynamic Pigovian type tax proposed in the paper. Such a tax resembles a specific tax plus an element that depends on the amount of remaining reserves. This resemblance means that, in practice, specific taxes may act as proxies for environmental taxes. The paper also points at complementarities and tradeoffs between economic and environmental concerns that could arise in reforming mineral taxes.